Compliance to Company Based Colorectal Cancer Screening in Germany using Fecal Immunochemical Test (FIT) - Results of Almost Half a Million FIT Tests - Pieper Claudia; Alkhalawi Eman; Reinholz Johannes; Gushin Dmitrii (Journal of Colon And Rectal Cancer, 2017)
Background Despite the existence of the statutory early cancer detection program in Germany and the removal of financial barriers, which is frequently reported in the literature to be the main obstacle in screening, uptake of colorectal cancer screening remains quite low. The campaign for colorectal cancer screening in German companies reported in this article started in 2010. It was initiated because of the low compliance with opportunistic public colorectal cancer screening efforts. Its goal is to improve participation by offering an organized screening program using a simple test (FIT). Methods An offer for company employees is publicized through posters, company newsletters and the intranet. The difference between the positivity rates of those who returned the kits within 20 days and later than 20 days was assessed using the Z-test. The average time between a positive result and colonoscopy was estimated using the Poincaré plot method. The positive predictive values were calculated for carcinomas, advanced adenomas or any lesions. The sensitivity and specificity of immoCare-C published by Vogel et al. and Hundt et al. were used to derive the confidence intervals for the positive likelihood ratio (for carcinoma and any kind of adenoma). Results A total of 312,147 kits were returned and analyzed (return rate 70.2%). 5.6% gave a positive result. The PPV for cancer aged between 55 and 74 was 4.6% for men and women (95% CI: 2.38%-6.76% and 1.28%-7.99%, respectively), but 22% for men (95% CI: 17.93%-26.65%) and 8% for women (95%CI: 3.63%-12.26%) for advanced adenomas. The PPV for any lesion was higher for those with familial risk (49.3%) and 42.6% for those without familial risk (95% CI: 40.2%-45.0%), but with overlapping confidence intervals. Conclusions The reported sample is not representative. Although, offering CRC screening in companies may be an effective way of increasing uptake in the target population. Differences in the test performance between men and women need further evaluation.
Keywords: colorectal cancer screening